Desertification in the northeast of Brazil: the natural resources use and the land degradation - Cavalcanti, Edneida Rabêlo; Coutinho, Solange Fernandes Soares (Sociedade & Natureza, 2005)
The Agenda 21 and the United Nations Convention for Desertification Combat defines desertification as the degradation of lands in arid regions, semi-arid and sub-wet dried, resulting from various factors, among them the weather variations and the human activities. This understanding, besides marking the geographical space to be taken into consideration, undoes with the clearly climatic view of the question and proves that desertification has its origin in complex interactions of physical factors, biologics, political, socials, cultural and economics. However, it’s necessary to recognize that there are generally more serious causes, as the poverty, that leaves no alternative for the husbandmen only get from land the maximum possible to supply the family’s immediate necessity even affecting its subsistence for a long time. In terms of world, semi-arid regions represent 1/3 of the planet’s surface, where lives 1/5 of the population, more than 1 million people. Twenty-two per cent is the participation of these areas in the production of foods. The Semi-arid of Brazil is registered as one of the physiographic zones of the Northeast Region, representing about 57% of this territory. The organization of the economical process, historically based on extensive cattle breeding and agriculture, and on the existence of some products of larger importance in the market, like the case of cotton was, always based on an agrarian structure dominated by land concentrations. In the more diffused desertification process in the North-eastern semi-arid this pattern has been constructed on alarming proportions, aggravated and reaffirmed by the occurrence of periodic droughts and the peculiarities due to the systems of production that appear from this process directly contrary to the correct manners of use of the natural resources, in option to, where and how to develop the agricultural activities.